Synthesis and characterization of bamboo leaf based carbon-opacified silica aerogel (COSA) / Kow Kien Woh - Kow, Kien Woh (2014)
Silica aerogel with extremely low thermal conductivity has great potential to be used as thermal insulating material. Its application is currently restricted by the expensive raw materials such as tetramethyl-orthosilicate (TMOS) and tetraethyl-orthosilicate (TEOS). In addition, pure silica aerogel has low absorption of infrared radiation at 3 – 8 μm and led to increase in thermal conductivity at high temperature. Carbon is commonly used as an opacifier in silica aerogel to absorb the radiation and therefore suppress thermal conductivity of aerogel. However, separated source of carbon is required for the opacification of aerogel. Biomass such as bamboo leaves and cogon grass contain both silica and carbon. They can provide both sources to synthesize carbon-opacified silica aerogel (COSA). The use of biomass in the synthesis of COSA not only can reduce the cost of expensive raw materials, but also to minimize agriculture waste. Hence, this work is aimed to synthesize COSA by using biomass as a single source of raw material. Effects of gelation pH, carbon loading, silica concentration and temperatures on the thermal conductivity of COSA were investigated and optimized by using statistical model. Its thermal insulative performance was compared with the silica aerogel synthesized via conventional method including TEOS and carbon black. The study revealed that thermal conductivity of silica aerogel opacified with activated carbon is comparable to those opacified with carbon black. The result showed that optimal carbon loading which minimized the thermal conductivity present at different temperatures. Such optimal loading increased as temperature applied to the opacified aerogel increased. Tie lines that optimized thermal conductivity at different temperatures were obtained for various combinations of carbon loading and silica concentration. Thermo-gravimetry (TGA) results of the aerogels also indicate that opacified aerogel is thermally stable up to 495 °C and therefore suitable be used at high temperature.